2006
DOI: 10.1063/1.2202742
|View full text |Cite
|
Sign up to set email alerts
|

Electronic states and luminescence in higher fullerene/porous Si nanocrystal composites

Abstract: Photoluminescence (PL) measurements have been performed on the nanocomposites of higher fullerene-coupled porous silicon (PS) nanocrystals. For the C70PS and C76(78)PS nanocomposites, the PL spectra show a pinning wavelength at approximately 565 nm and for the C84PS and C94PS nanosystems the pinning wavelength is at approximately 590 nm. The PL pinning property is closely related to the sorts of the coupled fullerenes. A band mixing model of direct and indirect gaps in a nanometer environment consisting of nc-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Soon after the demonstration of strong photoluminescence (PL) in nanostructured porous silicon [1], much effort has been devoted to elaborate silicon-based nanocomposite structures [2][3][4][5][6][7][8], either to realize multi-band emissions or to improve the PL stability and efficiency of the substrates. For example, copper [9], diamond [10], fullerene [11], Pb(Zr x , Ti 1−x )O 3 (PZT) [12], ZnSe [13], ZnS [14,15], ZnO [16,17], CdSe [18] and CdS [19][20][21][22] have been used as components to fabricate silicon-based nanocomposite structures, and unique optical properties have been achieved in these systems. As one of the promising II-VI compound semiconductors, cadmium sulfide (CdS) has been found to possess the properties of high electrical conductibility, broad-spectrum light transparency and high chemical stability [23][24][25][26][27][28], and has been much considered for potential applications in the fields of solar cells [23], optoelectronics [24][25][26] and microelectronics [27].…”
Section: Introductionmentioning
confidence: 99%
“…Soon after the demonstration of strong photoluminescence (PL) in nanostructured porous silicon [1], much effort has been devoted to elaborate silicon-based nanocomposite structures [2][3][4][5][6][7][8], either to realize multi-band emissions or to improve the PL stability and efficiency of the substrates. For example, copper [9], diamond [10], fullerene [11], Pb(Zr x , Ti 1−x )O 3 (PZT) [12], ZnSe [13], ZnS [14,15], ZnO [16,17], CdSe [18] and CdS [19][20][21][22] have been used as components to fabricate silicon-based nanocomposite structures, and unique optical properties have been achieved in these systems. As one of the promising II-VI compound semiconductors, cadmium sulfide (CdS) has been found to possess the properties of high electrical conductibility, broad-spectrum light transparency and high chemical stability [23][24][25][26][27][28], and has been much considered for potential applications in the fields of solar cells [23], optoelectronics [24][25][26] and microelectronics [27].…”
Section: Introductionmentioning
confidence: 99%
“…By measuring the friction force versus applied force for the Si (001) surface, it was shown that the friction coefficient is decreased for more than one order of magnitude, while silicon surface is covered by a C 60 thin film. There are some experimental works devoted to investigation of C 60 molecules implanted in porous silicon. In ref the authors observed an enhanced photoluminescence (PL) signal, in addition to the PL peak of porous Si, a peak at 730 nm caused by perfect C 60 molecules and other peaks at 620 and 630 nm caused by imperfect C 60 molecules. In the same work, unusual Raman features related to the C 60 molecular environments and disorder effects inside solid silicon were obtained with large intensities.…”
Section: Introductionmentioning
confidence: 99%
“…There are some experimental works devoted to investigation of C 60 molecules implanted in porous silicon. [6][7][8] In reference 6 the authors observed an enhanced photoluminescence (PL) signal, in addition to the PL peak of porous Si, a peak at 730 nm caused by perfect C 60 molecules and other peaks at 620 and 630 nm caused by imperfect C 60 molecules. In the same work, unusual Raman features related to the C 60 molecular environments and disorder effects inside solid silicon were obtained with large intensities.…”
Section: Fullerenes Possess Unique Mechanical Properties Chemical Inmentioning
confidence: 99%